The Effect of Attitudes, Awareness, and Knowledge of Taxpayers with Control of Village Officers as a Moderating Variable on Taxpayer Compliance - Nisma, Nisma; Kalsum, Ummu; Suun, Muhammad (Advances in Taxation Research, 2024)
Purpose: This study examines the influence of taxpayer attitudes, awareness, and knowledge on land and building tax compliance, with urban village officer control as a moderating variable. Understanding these factors is crucial for enhancing tax compliance and optimizing local tax revenue collection. Research Design and Methodology: The research adopts a quantitative approach using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) to analyze the relationships among variables. The study focuses on registered land and building taxpayers in Wajo District, Makassar, and examines the moderating role of urban village officer control. Data were gathered through structured questionnaires and analyzed using SmartPLS software to assess direct and moderating effects. Findings and Discussion: The results show that taxpayer attitudes, awareness, and knowledge positively and significantly affect tax compliance. Moreover, urban village officer control strengthens these relationships, increasing taxpayer adherence to regulations. These findings align with the Theory of Planned Behavior (TPB), which emphasizes the role of intention, attitude, and perceived control in shaping compliance behavior. Implications: The study contributes theoretically by extending tax compliance models to include regulatory control. Practically, it suggests that tax authorities should improve taxpayer education, service quality, and enforcement mechanisms. Strengthening urban village officer control as part of administrative enforcement can enhance compliance and optimize tax revenue collection.